Language and Framing In Russia-Ukraine Conflict News - Adisti, Stefani Ernes; Charima, Yunia Aqlia; Cahyono, Setyo Prasiyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
This study aims to describe the effect of the use of language and framing in the online newspaper. BBC news article entitled “Why has Russia Invaded Ukraine and What does Putin Want?” reported the Russian-Ukrainian conflict is chosen in establishing this study. In particular, this study employs qualitative method and adopts Entman’s (1993) framing theory. The result defines a problem related to Russia’s invasion towards Ukraine causing lives lost, people’s evacuation, and cities disintegration. The diagnosis cause refers to Russia's insecurity and inadequacy, due to Ukraine's bias towards the west, as constant threat. The moral judgement refers to Russia's assessment accuses Ukraine of intimidation and genocide, while the international community believed the term ‘a war crime and genocide’, questioned Russia’s inadequate declaration against Ukraine damaging Russia’s credibility. Negotiation appeared as a possibility to settle the Russian-Ukrainian conflict are the treatment recommendation. Essentially, language has power and framing takes control of public's perspective through report in the mass media; thus, journalistic caution is required in producing objective and educational news.